Electrochemical enhancement method for battery electrode

By preparing silicon-graphene gradient composite electrodes and doping them with Cu using magnetron sputtering technology, the volume expansion problem of silicon-based anode materials was solved, the electrochemical performance and stability of the battery were improved, and the battery life was extended.

CN119265528AActive Publication Date: 2025-01-07CHINA RAILWAY ELECTRIFICATION ENGINEERING GROUP CO LTD +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411803767.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-01-07
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

Existing technologies for preparing silicon-based anode materials suffer from battery failure due to volume expansion, and existing methods also have drawbacks such as high energy consumption, high cost, poor dispersion performance, or toxic and flammable raw materials.

Method used

A silicon-graphene gradient composite electrode was prepared by magnetron sputtering and doped with Cu. By alternating deposition of graphite and silicon layers and annealing, a multilayer structure was formed to alleviate volume expansion and improve conductivity.

Benefits of technology

It effectively alleviates the volume expansion of silicon-based anode materials during charging and discharging, improves the conductivity and cycle stability of the electrode, and extends the battery's lifespan.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of metal material plating, in particular to a battery electrode electrochemical enhancement method. According to the method, an electrode structure is prepared by adopting a magnetron sputtering process, an alternating structure of graphene and silicon is obtained, the conductivity and the cycling stability of the electrode can be improved due to the fact that the graphene has a huge surface area and is better in bonding performance with a current collector and a silicon layer, and the graphene molecular structure is a three-dimensional hollow structure and has a large elastic modulus, so that the conductivity and the cycling stability of the electrode are improved. And cyclic stress deformation generated by the silicon layer in the cyclic charging and discharging process can be absorbed, the sputtering power is gradually changed when a multi-layer structure is prepared, and the tendency of interlayer cracking can be avoided while deformation can be further relieved in a transition gradient mode. Cu is doped when the Si layer is prepared, Cu atoms cause lattice distortion in the Si layer, enough dislocation, vacancy and other defects are generated, a buffer space is provided for subsequent deformation, and the conductivity of the electrode is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal material plating, in particular to a method for enhancing the electrochemical properties of battery electrodes. Background Art

[0002] New energy has attracted much attention due to its clean, renewable and environmentally friendly characteristics, but there are still problems such as power supply stability and cost-effectiveness, which limit the large-scale application of new energy. Secondary batteries are currently the best choice for energy storage devices that can achieve continuous and stable power supply. They are also the most widely used energy storage devices. Their ability to effectively store and convert energy can meet people's growing energy needs and play an important role in production and life. There are many types of secondary batteries. Lithium-ion batteries, storage batteries, nickel-chromium batteries, etc. are all common secondary batteries. Among these secondary batteries, lithium-ion batteries stand out because of their environmental friendliness and excellent electrochemical properties. Good energy density and long cycle life enable lithium-ion batteries to cope with a variety of application scenarios, thus achieving a wide range of applications.

[0003] The key materials of the internal structure of lithium-ion batteries are composed of positive electrode materials, negative electrode materials, electrolyte materials and separator materials. The main function of positive electrode materials is to provide active lithium ions (Li + ); the main function of the negative electrode material is to store and release energy; the main function of the electrolyte is lithium ion (Li + ) conducts between the positive and negative electrodes; the main function of the separator is to prevent the positive and negative electrode materials from contacting and causing the battery to short-circuit. When the lithium-ion battery is charging, Li + Lithium ions are released from the positive electrode material and embedded in the negative electrode material after passing through the electrolyte medium. At the same time, electrons are transferred from the positive electrode to the negative electrode through an external circuit, converting electrical energy into storable chemical energy. When the battery is discharged, due to the potential difference between the positive and negative electrodes, lithium ions spontaneously escape from the negative electrode material and return to embed in the positive electrode material. At the same time, negative electrode electrons migrate back to the positive electrode through an external circuit, converting the stored chemical energy into electrical energy.

[0004] The negative electrode materials of lithium-ion batteries must meet the following conditions: low electrochemical reaction potential, strong lithium storage capacity, small change in voltage platform, high ion-electron conductivity, stable solid electrolyte interface membrane, low cost, simple preparation process, and environmental friendliness. Common negative electrode materials can be divided into carbon-based and non-carbon-based materials. The theoretical specific capacity of silicon-based materials is 4200 mAh·g -1, far higher than graphite, and with obvious advantages such as environmental friendliness, high abundance of earth elements, and easy processing, it is considered to be one of the most promising candidates for negative electrode materials and has attracted widespread attention. However, since silicon materials are prone to volume expansion, and the expansion deformation rate even exceeds 300%, the expansion and contraction stress generated during the charging and discharging process causes severe cracking of the silicon negative electrode, and then the battery accelerates to failure. The commercialization of silicon negative electrodes is subject to multiple obstacles. The best way to alleviate the above problems is to prepare silicon-carbon composite materials using high specific capacity silicon materials and high stability carbon materials.

[0005] There are many methods for preparing silicon-carbon composite negative electrode materials, including chemical vapor deposition, mechanical ball milling, spraying, magnesium thermal reduction, sol-gel, and pyrolysis. The spraying method has the disadvantages of high energy consumption and high instrument requirements; the magnesium thermal reduction method has the disadvantages of low discharge specific capacity; the sol-gel method has high cost; the pyrolysis method has the disadvantages of poor dispersion performance and serious agglomeration; the negative electrode material obtained by mechanical ball milling has a short service life; the raw materials used in chemical vapor deposition are toxic and flammable.

[0006] On this basis, the present application adopts magnetron sputtering technology to alternately prepare silicon-graphene gradient electrodes and dopes Cu, thereby overcoming the disadvantages of the preparation method in the prior art and improving the electrochemical performance of the electrode. Summary of the invention

[0007] A method for enhancing the electrochemical properties of a battery electrode comprises preparing a silicon-graphene gradient composite electrode by magnetron sputtering and doping the electrode with metal Cu.

[0008] First, the current collector is cleaned and dried, and then placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4 Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 8-12sccm. The current collector is PET, PP, PI or PC.

[0009] Then, a Si-graphene gradient alternating structure is prepared. The target materials used are a silicon target with a purity of 99.999%, a graphite target with a purity of 99.999%, and a Cu target with a purity of 99.999%. The sputtering power of the silicon target is 80-100W, the sputtering power of the graphite target is 80-100W, and the sputtering power of the copper target is 20-30W. At the beginning of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 15-25nm, and then the graphite target power is gradually reduced to 0W, and the sputtering power of the silicon target and the copper target is gradually increased to the preset value, and a 15-25nm thick Si layer is sputtered; the multilayer structure of the graphite layer and the silicon layer is alternately deposited in the above manner, and a gradient transition is achieved.

[0010] Finally, the alternating multilayer structure electrode was annealed to convert graphite into graphene, further reduce the internal stress generated during the sputtering process, and further improve the diffusion transition between graphene and Si layer. The background vacuum during annealing was 3.0×10 -4 pa, annealing at 300-400℃ for 20-30 minutes, and then naturally cooling to room temperature in vacuum to finally obtain a battery electrode with enhanced electrochemical properties.

[0011] The present invention firstly adopts a magnetron sputtering process to prepare an electrode structure, and obtains an alternating structure of graphene and silicon. Since the graphene surface area is huge, the bonding property with the current collector and the silicon layer is better, and the conductive performance and cycle stability of the electrode can be improved. Moreover, since the graphene molecular structure is a three-dimensional hollow structure, it has a large elastic modulus and can absorb the cyclic stress deformation generated by the silicon layer during the cyclic charge and discharge process. In addition, the sputtering power is gradually changed when preparing the multilayer structure, and the transition gradient method can further alleviate the deformation while avoiding the tendency of interlayer cracking. When the Si layer is doped with Cu, the Cu atoms cause lattice distortion inside the Si silicon layer, generate sufficient defects such as dislocations and vacancies, provide a buffer space for subsequent deformation, and further improve the conductive performance of the electrode. DETAILED DESCRIPTION

[0012] Embodiment 1: A method for enhancing the electrochemical properties of battery electrodes, firstly, the current collector is cleaned and dried, and then the current collector is placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4 Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 10sccm. Subsequently, a Si-graphene gradient alternating structure is prepared. The targets used are silicon targets with a purity of 99.999%, graphite targets with a purity of 99.999%, and Cu targets with a purity of 99.999%. The sputtering power of the silicon target is 100W, the sputtering power of the graphite target is 100W, and the sputtering power of the copper target is 30W. At the beginning of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 25nm. Then, the graphite target power is gradually reduced to 0W, and the sputtering power of the silicon target and the copper target is gradually increased to 100W and 30W, and a 25nm thick Si layer is sputtered; the multilayer structure of graphite layers and silicon layers is alternately deposited in the above manner, and a gradient transition is achieved. Finally, the alternating multilayer structure electrode is annealed, and the background vacuum during annealing is 3.0×10 -4 pa, annealed at 350℃ for 25 minutes, and then cooled naturally to room temperature in a vacuum state after annealing, finally obtaining a battery electrode with enhanced electrochemical properties.

[0013] The negative electrode of the battery was obtained by the above process, and the positive electrode used a lithium sheet. A three-component mixed solvent EC∶DMC∶EMC=1∶1∶1, v / v solution of 1mol / L LiPF6 was used as the electrolyte, and a polypropylene microporous membrane was used as the separator to assemble a CR2016 simulated battery for subsequent testing. The constant current charge and discharge test of the button battery was carried out using the Xinwei company test system. The steps of the cycle performance test were: first activate it with a current of 0.05 C for one cycle, and then charge and discharge it for 400 cycles at a current of 0.5 C, and measure the change in electrode size and discharge specific capacity. The test results are shown in Table 1.

[0014] Embodiment 2: A method for enhancing the electrochemical properties of battery electrodes, firstly, the current collector is cleaned and dried, and then the current collector is placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4 Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 10sccm. Subsequently, a Si-graphene gradient alternating structure is prepared. The targets used are silicon targets with a purity of 99.999%, graphite targets with a purity of 99.999%, and Cu targets with a purity of 99.999%. The sputtering power of the silicon target is 80W, the sputtering power of the graphite target is 80W, and the sputtering power of the copper target is 20W. At the beginning of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 20nm. Then, the graphite target power is gradually reduced to 0W, and the sputtering power of the silicon target and the copper target is gradually increased to 80W and 20W, and a 20nm thick Si layer is sputtered; the multilayer structure of graphite layers and silicon layers is alternately deposited in the above manner, and a gradient transition is achieved. Finally, the alternating multilayer structure electrode is annealed, and the background vacuum during annealing is 3.0×10 -4 pa, annealed at 350°C for 25 minutes, and cooled naturally to room temperature in vacuum after annealing, finally obtaining a battery electrode with enhanced electrochemical properties. The battery assembly and testing methods refer to Example 1.

[0015] Embodiment 3: A method for enhancing the electrochemical properties of battery electrodes, firstly, the current collector is cleaned and dried, and then the current collector is placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 10sccm. Subsequently, a Si-graphene gradient alternating structure is prepared. The targets used are silicon targets with a purity of 99.999%, graphite targets with a purity of 99.999%, and Cu targets with a purity of 99.999%. The sputtering power of the silicon target is 90W, the sputtering power of the graphite target is 90W, and the sputtering power of the copper target is 25W. At the beginning of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 20nm. Then, the graphite target power is gradually reduced to 0W, and the sputtering power of the silicon target and the copper target is gradually increased to 90W and 25W, and a 20nm thick Si layer is sputtered; the multilayer structure of graphite layers and silicon layers is alternately deposited in the above manner, and a gradient transition is achieved. Finally, the alternating multilayer structure electrode is annealed, and the background vacuum during annealing is 3.0×10 -4 pa, annealed at 350°C for 25 minutes, and cooled naturally to room temperature in vacuum after annealing, finally obtaining a battery electrode with enhanced electrochemical properties. The battery assembly and testing methods refer to Example 1.

[0016] Comparative Example 1: A method for enhancing the electrochemical properties of battery electrodes, firstly, the current collector is cleaned and dried, and then the current collector is placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4 Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 10sccm. Then, a Si-graphene gradient alternating structure is prepared. The targets used are a silicon target with a purity of 99.999% and a graphite target with a purity of 99.99%. The sputtering power of the silicon target is 80W, and the sputtering power of the graphite target is 80W. At the beginning of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 20nm. Then, the graphite target power is gradually reduced to 0W, and the silicon target sputtering power is gradually increased to 80W to sputter a 20nm thick Si layer; the graphite layer and the silicon layer multilayer structure are alternately deposited in the above manner, and a gradient transition is achieved. Finally, the alternating multilayer structure electrode is annealed, and the background vacuum during annealing is 3.0×10 -4 pa, annealed at 350°C for 25 minutes, and cooled naturally to room temperature in vacuum after annealing, finally obtaining a battery electrode with enhanced electrochemical properties. The battery assembly and testing methods refer to Example 1.

[0017] Comparative Example 2: A method for enhancing the electrochemical properties of battery electrodes, firstly, the current collector is cleaned and dried, and then the current collector is placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 10sccm. Subsequently, a Si-graphene gradient alternating structure is prepared. The targets used are a silicon target with a purity of 99.999%, a graphite target with a purity of 99.999%, and a Cu target with a purity of 99.999%. The sputtering power of the silicon target is 80W, the sputtering power of the graphite target is 80W, and the sputtering power of the copper target is 20W. At the beginning of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 20nm, and then the graphite target power is gradually reduced to 0W, and the sputtering power of the silicon target and the copper target is gradually increased to 80W and 20W, and a 20nm thick Si layer is sputtered; the graphite layer and the silicon layer multilayer structure are alternately deposited in the above manner, and a gradient transition is achieved, and finally an electrochemically enhanced battery electrode is obtained. The battery assembly and testing method refer to Example 1.

[0018] Comparative Example 3: A method for enhancing the electrochemical properties of battery electrodes, firstly, the current collector is cleaned and dried, and then the current collector is placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4 Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 10sccm. Subsequently, a Si-graphene gradient alternating structure is prepared. The targets used are silicon targets with a purity of 99.999%, graphite targets with a purity of 99.999%, and Cu targets with a purity of 99.999%. The sputtering power of the silicon target is 80W, the sputtering power of the graphite target is 80W, and the sputtering power of the copper target is 20W. At the beginning of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 20nm. Then the graphite target is turned off, and the silicon target and copper target are turned on with sputtering powers of 80W and 20W to sputter a 20nm thick Si layer; the multilayer structure of graphite layers and silicon layers is alternately deposited in the above manner, and a gradient transition is achieved. Finally, the alternating multilayer structure electrode is annealed, and the background vacuum during annealing is 3.0×10 -4 pa, annealed at 350°C for 25 minutes, and cooled naturally to room temperature in vacuum after annealing, finally obtaining a battery electrode with enhanced electrochemical properties. The battery assembly and testing methods refer to Example 1.

[0019] Comparative Example 4: A method for enhancing the electrochemical properties of battery electrodes, firstly, the current collector is cleaned and dried, and then the current collector is placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 10sccm. Then, a Si-graphene gradient alternating structure is prepared. The targets used are silicon targets with a purity of 99.999%, graphite targets with a purity of 99.999%, and Cu targets with a purity of 99.999%. The sputtering power of the silicon target is 80W, the sputtering power of the graphite target is 80W, and the sputtering power of the copper target is 10W. At the beginning of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 20nm. Then, the graphite target power is gradually reduced to 0W, and the sputtering power of the silicon target and the copper target is gradually increased to 80W and 10W to sputter a 20nm thick Si layer; the multilayer structure of graphite layers and silicon layers is alternately deposited in the above manner, and a gradient transition is achieved. Finally, the alternating multilayer structure electrode is annealed, and the background vacuum during annealing is 3.0×10 -4 pa, annealed at 350°C for 25 minutes, and cooled naturally to room temperature in vacuum after annealing, finally obtaining a battery electrode with enhanced electrochemical properties. The battery assembly and testing methods refer to Example 1.

[0020] Comparative Example 5: A method for enhancing the electrochemical properties of battery electrodes, firstly, the current collector is cleaned and dried, and then the current collector is placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10 -4 Pa, the working gas is high-purity argon with a purity of 99.999%, and the flow rate of argon is 10sccm. Subsequently, a Si-graphene gradient alternating structure is prepared. The targets used are silicon targets with a purity of 99.999%, graphite targets with a purity of 99.999%, and Cu targets with a purity of 99.999%. The sputtering power of the silicon target is 80W, the sputtering power of the graphite target is 80W, and the sputtering power of the copper target is 40W. At the beginning of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 20nm. Then, the graphite target power is gradually reduced to 0W, and the sputtering power of the silicon target and the copper target is gradually increased to 80W and 40W to sputter a 20nm thick Si layer; the multilayer structure of graphite layers and silicon layers is alternately deposited in the above manner, and a gradient transition is achieved. Finally, the alternating multilayer structure electrode is annealed, and the background vacuum during annealing is 3.0×10 -4 pa, annealed at 350°C for 25 minutes, and cooled naturally to room temperature in vacuum after annealing, finally obtaining a battery electrode with enhanced electrochemical properties. The battery assembly and testing methods refer to Example 1.

[0021] Table 1 Test results .

Claims

1. A method for enhancing the electrochemical properties of a battery electrode, characterized in that: First, the current collector is placed in a vacuum magnetron sputtering chamber. The background vacuum of the sputtering chamber is better than 2.0×10-4 Pa. The working gas is high-purity argon with a purity of 99.999% and a flow rate of 8-12sccm. Subsequently, a Si-graphene gradient alternating structure is prepared, the sputtering power of the silicon target is 80-100W, the sputtering power of the graphite target is 80-100W, and the sputtering power of the copper target is 20-30W. At the initial stage of sputtering, the graphite target is turned on to sputter a graphite layer with a thickness of 15-25nm, and then the graphite target power is gradually reduced to 0W, and the sputtering power of the silicon target and the copper target is gradually increased to a preset value to sputter a Si layer with a thickness of 15-25nm. In the above manner, a multilayer structure of graphite layers and silicon layers is alternately deposited, and a gradient transition is achieved; Finally, the alternating multilayer structure electrode is annealed at 300-400℃ for 20-30 minutes and then naturally cooled to room temperature.

2. The method according to claim 1, characterized in that The purity of the silicon target material used is 99.999%.

3. The method according to claim 1, characterized in that The purity of the graphite target used is 99.99%.

4. The method according to claim 1, characterized in that The purity of the Cu target material used is 99.999%.

5. The method according to claim 1, characterized in that The collecting fluid is PET, PP, PI or PC.

6. The method according to claim 1, characterized in that After annealing, the vacuum was maintained during natural cooling to room temperature.

7. The method according to claim 1, characterized in that The background vacuum during annealing is 3.0×10 -4 pa.

8. The method according to claim 1, characterized in that The current collector is cleaned and dried before being placed in the vacuum magnetron sputtering chamber.

9. The battery electrode improved by the enhancement method as claimed in claim 1.

10. The battery electrode according to claim 9, characterized in that The collecting fluid is PET, PP, PI or PC.

Citation Information

Patent Citations

  • Cathode material for lithium ion battery tin / carbon nanometer multilayer film, and preparation method and application thereof

    CN101414674A

  • Amorphous carbon coating and preparation method and application thereof

    CN101444985A

  • Method for preparing graphene membrane

    CN101913598A

  • Composite graphene lithium ion battery and manufacturing method for composite graphene electrode

    CN107742746A

  • Preparation method for copper-doped multilayer graphene

    CN108251808A